2021
DOI: 10.1111/jpc.15691
|View full text |Cite
|
Sign up to set email alerts
|

Sleep‐disordered breathing in Australian children with Prader‐Willi syndrome following initiation of growth hormone therapy

Abstract: Aim In children with Prader‐Willi syndrome (PWS), growth hormone (GH) improves height and body composition; however, may be associated with worsening sleep‐disordered breathing (SDB). Some studies have reported less SDB after GH initiation, but follow‐up with polysomnography is still advised in most clinical guidelines. Methods This retrospective, multicentre study, included children with PWS treated with GH at seven PWS treatment centres in Australia over the last 18 years. A paired analysis comparing polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…We also were unable to collect information of growth hormone therapy (GHT) and body mass index (BMI). Existing data suggests a complex relationship between sleep apnea, GHT, and BMI in PWS ( 72 77 ) with some studies showing associations and others not. However, since our analyses studied multiple dimensions of sleep, it is unclear if inclusion of these variables would impact our results.…”
Section: Discussionmentioning
confidence: 99%
“…We also were unable to collect information of growth hormone therapy (GHT) and body mass index (BMI). Existing data suggests a complex relationship between sleep apnea, GHT, and BMI in PWS ( 72 77 ) with some studies showing associations and others not. However, since our analyses studied multiple dimensions of sleep, it is unclear if inclusion of these variables would impact our results.…”
Section: Discussionmentioning
confidence: 99%
“…However, a small subset of patients (2 patients in the younger group, 1 patient in the older group) developed moderate or severe OSA 3 months after starting rhGH. Similarly, Caudri et al 41 also showed no statistically significant differences in baseline and follow up OAHI among 94 children with PWS after rhGH initiation. Yet, it is notable that 12 subjects (13%) had no or mild OSA at baseline yet progressed to moderate or severe OSA which altered their clinical management after rhGH.…”
Section: Growth Hormone Therapymentioning
confidence: 91%
“…Ultimately, this led authors to advocate for close OSA monitoring (eg, home pulse oximetry) in infants with PWS and respiratory illness on rhGH. Regarding central apneic events, most studies 15,[41][42][43] demonstrate improvement following rhGH initiation. In the absence of placebo-controlled trials, it is not known whether these improvements would have been seen regardless of rhGH due to natural physiologic maturation.…”
Section: Growth Hormone Therapymentioning
confidence: 99%
“…GH therapy can result in improvement in ventilatory control and inspiratory drive [39]. In an Australian multicenter retrospective study, there was no significant increase in median oAHI following initiation of GH in children with PWS [43]. One study showed worsening of sleep disturbance after initiation of GH therapy; however, on average, affected patients had higher IGF-1 levels and respiratory issues, so they may have had other causes of morbidity [28].…”
Section: Growth Hormone Therapymentioning
confidence: 99%